Challenges and Barriers to Telemedicine Implementation (International Journal of Progressive Research and Innovation in Science, Engineering, Technology, Commerce, Management and Law (IJPRISETCML), 2025)
The literature highlights various challenges and barriers to telemedicine implementation, emphasizing the need for targeted strategies to address these issues effectively. Addressing these barriers is crucial for enhancing telemedicine's effectiveness and ensuring equitable access to healthcare services for all patients. To achieve successful telemedicine implementation, it is essential to recognize and tackle systemic barriers, including infrastructure limitations, regulatory challenges, and disparities in digital literacy among different populations
Keywords: AI; ML; Health System; Algorithms; Telemedicine